APOE-ε4 Is Associated With Reduced Verbal Memory Performance and Higher Emotional, Cognitive, and Everyday Executive Function Symptoms Two Months After Mild Traumatic Brain Injury - Hellstrøm, Torgeir; Andelic, Nada; Holthe, Øyvor Øistensen; Helseth, Eirik; Server, Andres; Eiklid, Kristin; Sigurdardottir, Solrun (Frontiers in Neurology, 2022)
Background: Substantial variance exists in outcomes after mild traumatic brain injury (MTBI), and these differences are not fully explained by injury characteristics or severity. Genetic factors are likely to play a role in this variance. Objectives: The aim of this study was to examine associations between the apolipoprotein (APOE)-ɛ4 allele and memory measures at two months post-MTBI and to evaluate whether subjective cognitive and affective symptoms were associated with APOE-ɛ4 status. Based on previous research, it was hypothesized that APOE-ɛ4 carriers would show poorer verbal memory performance compared to APOE-ɛ4 non-carriers. Methods: Neuropsychological data at two months post-injury and blood samples that could be used to assess APOE genotype were available for 134 patients with MTBI (mean age 39.2 years, 62% males, 37% APOE-ɛ4 carriers). All patients underwent computed tomography at hospital admission and magnetic resonance imaging four weeks post-injury. Results: The APOE-ɛ4 + status was associated with decreased immediate memory recall (p=0.036; β= -0.10, 95% CI [-0.19, -0.01]). Emotional, cognitive, and everyday executive function symptoms at two months post-injury were significantly higher in APOE-ɛ4 carriers compared to non-carriers. Conclusion: The APOE-ɛ4+ allele has a negative effect on verbal memory and symptom burden two months after MTBI.